The coat - Hunt, Julie, 1958-; Brooks, Ron, 1948- (Crows Nest, NSW : Allen & Unwin, 2012)
The Coat stood in a paddock at the end of a row of strawberries. It was buttoned up tight and stuffed full of straw and it was angry. 'What a waste of me!' it yelled. Then along came a man. 'I could do with a coat like that,' the man said. Together, swooping and swinging, they travelled to the Cafe Delitzia, and had the night of their lives.
For primary school age.
Keywords: Coats -- Juvenile fiction; Magic -- Juvenile fiction; Australian; Children's stories